Effect of temporal stimulus properties on the nociceptive detection probability using intra-epidermal electrical stimulation - Doll, Robert J. (Exp Brain Res, 2015)
Chronic pain disorders can be initiated and maintained by malfunctioning of one or several mechanisms underlying the nociceptive function. Although several quantitative sensory testing methods exist to characterize the nociceptive function, it remains difficult to distinguish the contributions of individual mechanisms. Intra-epidermal electrical stimulation of nociceptive fibers allows defining stimuli with temporal properties within the timescale of these mechanisms. Here, we studied the effect of stimulus properties on the psychophysical detection probability. A psychophysical detection experiment was conducted including 30 healthy human participants. Participants were presented with electrical stimuli having various temporal properties. The pulse-width was varied for single pulse stimuli (either 420 or 840 μs), and the inter-pulse interval for double pulse stimuli (10, 50, or 100 ms). Generalized linear mixed models were used to obtain estimates of thresholds and slopes of the psychophysical function. The 840-μs single pulse resulted in a lower threshold and steeper slope of the psychophysical function than the 420-μs single pulse. Moreover, a double-pulse stimulus resulted in a lower threshold and steeper slope than single pulse stimuli. The slopes were similar between the double pulse stimuli, but thresholds slightly increased with increasing inter-pulse intervals. In the present study, it was demonstrated that varying the temporal properties of intra-epidermal electrical stimuli results in variations in nociceptive processing. The estimated thresholds and slopes corresponding to the selection of temporal properties suggest that contributions of peripheral and central nociceptive mechanisms can be reflected in psychophysical functions.